Analysis of the status quo of perioperative antibiotic prophylaxis in dermatosurgery in Germany: results of the DESSI‐study. (24th May 2019) - Balakirski, Galina; Felcht, Moritz; Bayer, Hans; Schmitt, Laurenz
Summary: Background: Perioperative antibiotic prophylaxis (PAP) is recommended for the prevention of postoperative infections by the Commission for Hospital Hygiene and Infection Prevention (KRINKO) at the Robert Koch Institute. However, how PAP is currently used in the field of dermatosurgery in Germany is unclear. Methods: All members of the German Society for Dermatosurgery (DGDC) were asked to participate in a web‐based survey in order to investigate the use of PAP by German dermatological surgeons. Results: 78 DGDC members completed the questionnaire. Of these, 89.7 % (70/78) were medical specialists with a median work experience of 15 years in the field of dermatosurgery, and 53.8 % (42/78) of the respondents regularly use PAP in dermatosurgery. Of these, 35.7 % (15/42) reported that they perform PAP for immunocompromised patients. Only a small proportion of skin surgeons stated that they administer PAP parenterally (5.9 %, 4/67). The most commonly used drug was cephalosporin cefuroxime. The duration of the PAP varied between single‐dose and prolonged administration for more than five days. Conclusion: Currently, the use of PAP in dermatosurgical procedures in Germany is not standardized. Prospective randomized dermatosurgical studies are needed in order to investigate whether the PAP recommendations of KRINKO are applicable to the field of dermatological surgery.